Evaluation of brand relationship quality using formative index: a novel measurement approach. Issue 4 (18th November 2019) - Adhikari, Kishalay; Panda, Rajeev Kumar
Abstract : Purpose: This paper aims to develop a parsimonious and robust formative index for evaluating and measuring the brand relationship quality of automobile brands. Design/methodology/approach: Survey questionnaires were used to collect empirical data from 395 car owners, out of which 362 samples were included in the final analysis. Partial least squares technique was used for index construction. Findings: The empirical findings exhibit that the automobile brand relationship quality (ABRQ) index based on the final set of six indicators effectively captures the conceptual domain of brand relationship quality. In addition, the external validity check affirms positive and significant influence of ABRQ index toward enhancing customer loyalty. Practical implications: ABRQ index can assist the brand managers and academicians for benchmarking and market strategy formulation while contributing to the limited literature on brand relationship quality. Also, this index having six-indicators can considerably reduce the time and effort of respondents for filling the questionnaires, in turn, improving response rates. Originality/value: This study represents a novel attempt to formulate a brand relationship quality index using formative measurement indicators, and as per the authors' knowledge, has not been attempted by prior researchers in this domain.